2011
DOI: 10.1037/a0023398
|View full text |Cite
|
Sign up to set email alerts
|

Goals, feedback, and self-regulation: Control theory as a natural framework for executive coaching.

Abstract: The popularity of coaching continues to grow at a rate faster than research can validate coaching practices. Although strong research and theory on coaching have been emerging over the past few years, we believe that this body of literature would benefit from more integration of theory and application of organizing frameworks. The current paper seeks to contribute to the coaching literature by applying a Control Theory (CT) framework to elements of executive coaching. The two core elements of CT-goals and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 74 publications
0
31
0
3
Order By: Relevance
“…These findings were inconsistent with [7,23,24] who emphasized that coaching is a form of professional learning which integrates the most effective learning about teacher work. This was supported by [10,25,26] who asserted that coaching is designed to integrate effective staff development and successful change management processes through providing a continuous growth process for people at all experience levels. This also agreed by (Clutterbuck 2011; Margaret 2017) who found that coaching is a way of working with colleagues to support and encourage them in their development [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were inconsistent with [7,23,24] who emphasized that coaching is a form of professional learning which integrates the most effective learning about teacher work. This was supported by [10,25,26] who asserted that coaching is designed to integrate effective staff development and successful change management processes through providing a continuous growth process for people at all experience levels. This also agreed by (Clutterbuck 2011; Margaret 2017) who found that coaching is a way of working with colleagues to support and encourage them in their development [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…Diese Auftragsklärung beinhaltet eine Operationalisierung der angestrebten Lösung für berufliche Anliegen, für die der Klient sich einen Fortschritt wünscht. Ziele zu setzen ist eine der wichtigsten Komponenten im Coaching (Gregory et al 2011).…”
Section: Karriereoptimismus Als Psychologische Ressource Fördernunclassified
“…Auch danach wurde nicht gefragt, ob das Handeln der beratenden Person hilfreich war, gerade hohe Ziele zu setzen, da die Hilfe beim Festlegen von hohen Zielen ein wichtiger Aspekt des Coachings ist (vgl. Gregory et al, 2011 Unter anderem stellen Bachelor-oder Masterarbeiten "Standortbestimmungen und Rückmeldungen in einem Lernprozess dar und sichern die Zielerreichung von Ausbildungen" (Tremp & Reusser, 2007, S. 5). Portfolios sind ein gängiges Mittel, um dies sicherzustellen.…”
Section: Arbeitsverhältnisses Derunclassified